2001
DOI: 10.1053/jvet.2001.28438
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Anatomy of the Equine Temporomandibular Joint

Abstract: Conditions affecting the lateral and caudal aspects of the dorsal compartment of the TMJ should be visible by arthroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
101
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(102 citation statements)
references
References 12 publications
0
101
1
Order By: Relevance
“…The dorsal and ventral compartments do not appear to communicate (May et al . ; Rodriguez et al . ), although one previous cadaver study showed communication (Rosenstein et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dorsal and ventral compartments do not appear to communicate (May et al . ; Rodriguez et al . ), although one previous cadaver study showed communication (Rosenstein et al .…”
Section: Discussionmentioning
confidence: 99%
“…The parotid salivary gland is in close proximity to the joint and may overlie the caudal part of the joint (May et al . ; Rosenstein et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly, several studies have been performed to evaluate the suitability and potential relevance of advanced imaging techniques, i.e. radiography (Ebling et al, 2009), computed tomography (Rodríguez et al, 2008;Carmalt et al, 2016), ultrasonography (Rodríguez et al, 2007), magnetic resonance imaging (Rodríguez et al, 2010) and TMJ-arthroscopy (May et al, 2001;Weller et al, 2002). Besides these diagnostic and gross anatomical investigations, functional examinations of the equine masticatory movements have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nondescript signs, it is possible that cases of TMJ‐DJD are either missed or incorrectly diagnosed (May et al . ; Rodriguez et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…In both horses and people, a common cause of TMJ‐DJD is trauma, which can lead to fracture of the mandibular condyle, disrupting the articular surface (May et al . ; Carmalt and Wilson ; Rodriguez et al . ; He et al .…”
Section: Introductionmentioning
confidence: 99%